2024
DOI: 10.1001/jamaneurol.2023.4737
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Cortical Lesions and the Central Vein Sign in Multiple Sclerosis

Alessandro Cagol,
Rosa Cortese,
Muhamed Barakovic
et al.

Abstract: ImportanceMultiple sclerosis (MS) misdiagnosis remains an important issue in clinical practice.ObjectiveTo quantify the performance of cortical lesions (CLs) and central vein sign (CVS) in distinguishing MS from other conditions showing brain lesions on magnetic resonance imaging (MRI).Design, Setting, and ParticipantsThis was a retrospective, cross-sectional multicenter study, with clinical and MRI data acquired between January 2010 and May 2020. Centralized MRI analysis was conducted between July 2020 and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
3
3
0
Order By: Relevance
“…As in previous studies, 8 , 40 , 42 we found CL in the majority of MS cases and only rarely in non-MS cases. When compared with the proportion of CVS-positive lesions, the presence of a single CL provided high specificity but only moderate sensitivity for MS diagnosis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As in previous studies, 8 , 40 , 42 we found CL in the majority of MS cases and only rarely in non-MS cases. When compared with the proportion of CVS-positive lesions, the presence of a single CL provided high specificity but only moderate sensitivity for MS diagnosis.…”
Section: Discussionsupporting
confidence: 90%
“…As expected, 7 , 9 , 39 , 40 a higher proportion of CVS-positive lesions was found in patients with MS compared with non-MS, resulting in high diagnostic sensitivity and specificity with an optimal CVS-positive lesion frequency cutoff of 41%, which is similar to the previously proposed “40% rule”. 9 , 22 , 23 ⁠ However, the exceptional CVS diagnostic performance and the specific CVS-positive lesion cutoff reported in our study is likely due to the adoption of the same optimized submillimetric 3D T2*-EPI sequence in all participating centers, 14 , 15 with minimal parameter adjustments and centralized postprocessing analysis.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A cut-off of 40% CVS positive lesions of the total amount of white matter lesions has been proposed as a biomarker able to discriminate between MS and non-MS conditions [ 63 ]. In a recent cross-sectional study [ 64 ] involving 1051 participants with variable inflammatory and non-inflammatory disorders, the adherence to the 40% CVS rule showed superior performance compared to the contribution of infratentorial, juxtacortical, and periventricular lesions in aiding the diagnosis of MS [ 64 ]. Other studies, instead, such as Maggi et al, used the 50% CVS cut-off to distinguish MS from vasculopathies [ 65 ].…”
Section: Iron-derived Imaging and Chronic Inflammationmentioning
confidence: 99%
“…Other studies, instead, such as Maggi et al, used the 50% CVS cut-off to distinguish MS from vasculopathies [ 65 ]. Consequently, CVS is highly promising in effectively distinguishing MS from other conditions associated with nonspecific white matter lesions [ 64 , 65 ].…”
Section: Iron-derived Imaging and Chronic Inflammationmentioning
confidence: 99%